A versatile current source for low, middle frequencies and interferential pulse therapies - Oliveira, Paulo Henrique de (2012)
Electrical stimulation is an important tool in medicine with applications like muscle rehabilitation, pain management and pacemakers. Portable stimulation devices for home use are divided mainly in two domains: low and middle frequency therapies. Due to the lack, in Germany, of a system to provide both therapies at the same equipment, the main objective of this project is the development of a current source not only capable of that, but also able to generate arbitrary stimulation patterns controlled by an external microcontroller. Moreover, the system should make possible the use of interferential current therapy. The result of the project is an electronic device that triggers current stimulation patterns based on three control signals, which could be easily generated by a microcontroller. The system provides LF stimulation with balanced current pulses up to 80mA through 1k? load impedance, pulse widths between 50 and 1000µs, and frequencies up to 150Hz. It also provides MF stimulation outputs up to 100mApp, with a modulation frequency up to 4kHz and a simple interface to control the envelope waveform. It presents also two galvanic isolated channels to allow interferential current therapy and, when no output current is intended, it is able to provide a short circuit on the load to remove possible net charges introduced by the system to the patient’s body. Additionally, a MATLAB application and a SPICE simulation were developed to assist the creation of control signals. As the system is able to deliver stimulation currents with an arbitrary pattern, it can be used to find the best pulse waveforms for a series of different applications involving electrical therapy, like TENS and MES.